Reflexões acerca do protagonismo negro: o Auto do Boi no Festival Folclórico de Parintins - Rego, Karine Maia (Brasil, 2025)
This article analyzes the Parintins Folk Festival, focusing on the theatrical performance of Auto do Boi and, within this context, Afro-Brazilian representation, emphasizing the characters Father Francisco and Mother Catirina as participants in the spectacle. The concern lies in the fact that, despite being mandatory Items in the presentation according to the Festival’s Regulations, these characters do not score points as other Auto do Boi Items – such as Amo do Boi, Sinhazinha da Fazenda, Pajé and Boi. Based on bibliographic research and interviews with performers and festival organizers, it was explored their historical origins, the marginalization of Black characters, as well as the pedagogical implications of their representations, seeking reasons and possible inclusive alternatives to Afro-Brazilian in this context.